1988
DOI: 10.1037/0033-2909.103.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Motor illusions: What do they reveal about proprioception?

Abstract: Five illusions involving distortions in the perception of limb position, movement, and weight are described in the context of their contribution to understanding the sensory processes involved in proprioception. In particular, these illusions demonstrate that the position sense representation of the body and the awareness of limb movement result from the cross-calibration of visual and proprioceptive signals. Studies of the vibration illusion and phantom-limb phenomenon indicate that the perception of limb mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 116 publications
(284 reference statements)
2
48
0
Order By: Relevance
“…With respect to other illusions reviewed by Jones (1988), aspects of the present results conform to the so-called phenomenon of postural persistence investigated by Hoff and Schilder (1925), Selling (1930), andJackson (1954). Specifically, in Experiments I and 2 the forearm with Splints Sand S· was judged horizontal when it was above the horizon.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…With respect to other illusions reviewed by Jones (1988), aspects of the present results conform to the so-called phenomenon of postural persistence investigated by Hoff and Schilder (1925), Selling (1930), andJackson (1954). Specifically, in Experiments I and 2 the forearm with Splints Sand S· was judged horizontal when it was above the horizon.…”
Section: Discussionsupporting
confidence: 62%
“…The effect of rotating {ed relative to {(Jd parallels a number of so-called illusory effects oflimb position that occur as a result of tendon vibration of a secured arm and as a result of a briefly sustained prior limb position (see Jones, 1988, for a review). A vibrated limb is felt to be at a position other than its actual spatial position.…”
Section: Discussionmentioning
confidence: 99%
“…If displacement in a direction not aligned with implied gravitational attraction is measured, target size does not influence displacement, whereas if displacement in the direction aligned with implied gravitational attraction is measured, larger targets exhibit larger downward displacement, regardless of the direction of target motion (for ascending targets, a smaller forward displacement is exhibited in memory for larger targets, and this is consistent with the general notion that larger targets are remembered as being lower in the display). Given that visually larger objects are usually perceived to be heavier (i.e., the size-weight illusion; Koseleff, 1957; for a review, see Jones, 1988), this pattern suggested that displacement was influenced by the implied weight of the target, rather than by the implied mass of the target. Weight is experienced along the axis aligned with gravitational attraction (weight ϭ mass ϫ acceleration due to gravity) and reflects the subjective experience of mass for observers whose lifetimes have been spent within a gravitational field of constant strength (as found on the surface of the Earth).…”
Section: Characteristics Of the Targetmentioning
confidence: 99%
“…The influence of peripheral afferent signals from muscles on perception of the body is investigated by directly changing proprioceptive signals, using muscle vibration. When the tendon of a limb is vibrated at 80 Hz [5][6][7] , the illusion of movement is created, even though the limb is not actually moving [8][9][10][11] . The illusion is elicited, because the vibration of the tendon activates the muscle spindles in a similar manner, as when the muscle is actually stretched 6,7,12) .…”
Section: The Role Of Single Sensory Signalsmentioning
confidence: 99%